Banking activities in the light of banking acts, part 1 (Discourse of Law and Administration, 2022)
Banking activities are the basic and essential element of the bank’s activity. However, this concept is not defined by the legislator, and the catalog of banking activities, due to its complex structure and the inclusion of banking activities in several acts, raises certain doubts in the literature on the subject. In the literature, banking activities are often replaced by the term banking services. The aim of the article is to present the views of the doctrine in this area and an attempt to systematize this knowledge.
Keywords: bank; banking activities; bank activity; banking services; outsourcing; mortgage banks; cooperative banks